2004
DOI: 10.1603/0022-2585-41.1.74
|View full text |Cite
|
Sign up to set email alerts
|

Circulating IgE in Patients with Ordinary and Crusted Scabies

Abstract: Serum from seven patients with ordinary scabies and six with crusted scabies were screened by immunoblotting for IgE- and IgG-specific proteins in an extract of the mite, Sarcoptes scabiei variety canis. Sera from atopic individuals without sensitivity to house dust mites were used as controls. Serum from all of the patients with crusted scabies showed strong IgE binding to 11-21 and IgG binding to 1-7 scabies proteins. In contrast, three of the seven patients with ordinary scabies showed IgE binding to one to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 25 publications
1
44
0
3
Order By: Relevance
“…Previous studies have used aqueous extracts of scabies mite whole body homogenates to demonstrate that these mites are the sources of many antigenic and allergenic proteins (Arlian et al 1988a(Arlian et al , 1991(Arlian et al , 1996b(Arlian et al , 2004aMorgan and Arlian 1994;Morgan et al 1997;Arlian and Morgan 2000;Schumann et al 2001) as well as to demonstrate that these mites produce molecules that are able to modulate the immune response of an infested host (Arlian et al 1996c(Arlian et al , 2003(Arlian et al , 2004a(Arlian et al , 2007Elder et al 2006Elder et al , 2009Lalli et al 2004;Bergstrom et al 2009;Arlian 2009, 2010;Mullins et al 2009;Mika et al 2012;Morgan et al 2013;Reynolds et al 2014;Swe and Fischer 2014). The molecules responsible for the observed antigenic and immunomodulatory activities of scabies mite extracts have not been identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have used aqueous extracts of scabies mite whole body homogenates to demonstrate that these mites are the sources of many antigenic and allergenic proteins (Arlian et al 1988a(Arlian et al , 1991(Arlian et al , 1996b(Arlian et al , 2004aMorgan and Arlian 1994;Morgan et al 1997;Arlian and Morgan 2000;Schumann et al 2001) as well as to demonstrate that these mites produce molecules that are able to modulate the immune response of an infested host (Arlian et al 1996c(Arlian et al , 2003(Arlian et al , 2004a(Arlian et al , 2007Elder et al 2006Elder et al , 2009Lalli et al 2004;Bergstrom et al 2009;Arlian 2009, 2010;Mullins et al 2009;Mika et al 2012;Morgan et al 2013;Reynolds et al 2014;Swe and Fischer 2014). The molecules responsible for the observed antigenic and immunomodulatory activities of scabies mite extracts have not been identified.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of immunoblotting studies have reported the molecular weights of various antigens recognized by the antibodies in the serum from scabies-infested hosts Arlian et al 1996aArlian et al , 2004aMorgan et al 1997;Arlian and Morgan 2000;Schumann et al 2001;Tarigan and Huntley 2005;Yadav et al 2006;Zalunardo et al 2006;Casais et al 2007;Rambozzi et al 2007;Rodriguez-Cadenas et al 2010;Hejduk et al 2011;Jakubek et al 2012). Yet little data identifying the proteins involved have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Studies document that scabies mite infestation causes the production of measurable antibodies in infested host species (4,40). Furthermore, host IgG has been demonstrated in the anterior midgut and esophagus of fresh mites (94,114).…”
Section: Antibody Detectionmentioning
confidence: 99%
“…Western blotting with plasma from these patients demonstrated that 6 of 7 individuals had strong IgE binding to S. scabiei var. canis protein extracts (2). Immunochemical studies have previously demonstrated that sera from rabbits infested with S. scabiei var.…”
mentioning
confidence: 99%